USING ROLE PLAY IN TEACHING SPEAKING AT THE THIRD YEAR STUDENTS OF SMP ISLAM RUHAMA CIREUNDEU (UNMUH BABEL PRESS, 2020)
This research is aimed to know whether Role Play Technique is effective in improving student’s speaking skill at 9th grade students of SMP Islam Ruhama Cireundeu. This research is based on the last observation result that the students were still difficult to speak. This research is categorized as Experimental Study. It is carried out to solve students’ problem in speaking. The findings of the research stated that students’ comprehension (66) is the lowest score and students’ grammar (66.5) is the highest score in post test score of experiment class while students’comprehension (72.5) is the lowest score and students’ vocabulary (74) is the highest score in post test of experiment class. The subject of this research is the students of class IX.1 and IX.2 of SMP Islam Ruhama Cireundeu. In collecting the data, this research uses observation and test. Based on the result and the discussion of this research, it can be said that the using of role play in teaching speaking is successful since the crieteria of success were achieved. The criteria of success is there is a significant improvement from pretest result to posttest. The result shows that the pretest average score in experiment class is 66.2 becomes 73.1 in post test while in control class, the significant improvement is only 1.2 (pre test 65.9 and post test 67.1). Based on the result that is mentioned before, the writer suggests that the English teacher should implement a role play in order to improve students’ speaking skill.